Virtual Reality, Augmented Reality and Artificial Intelligence in Special Education: A Practical Guide to Supporting Students with Learning Differences, 1st edition - Anderson, Ange (Routledge, 2020)
New technologies and ongoing developments in the fields of Virtual reality, augmented reality and artificial intelligence are changing the ways in which we facilitate learning. Recognising the positive role these technologies can play in the learning and progress of students assessed as having special educational needs, this practical guide explains the characteristics, benefits, risks and potential applications of new technologies in the classroom.